Wing-In-Ground-Effect (WIGE) Craft in Labuan Bajo, Is It Feasible? - Erna Mei Lestari; Fristi Bellia Annishia; Abdy Kurniawan (Warta Penelitian Perhubungan, 2025)
As an archipelagic country, Indonesia has many tourism destinations, including Komodo National Park (KNP) in Labuan Bajo, East Nusa Tenggara, which is promoted as a strategic area of tourism in Indonesia. Tourism is an integrated activity that requires transportation support to facilitate the mobility of tourists from one location to another. Given its archipelagic geographical characteristics, the use of ships for passenger transportation is very suitable in KNP, Labuan Bajo. One type of vessel that is currently widely used for commercial and tourism transportation is the Wing-In-Ground-Effect (WIGE) craft. Until now, WIGE craft has never been operated in Labuan Bajo KNP. As an investment, operating a ship in a certain area requires a feasibility assessment. Based on this background, this study analyzed the feasibility of operating the WIGE craft in KNP, Labuan Bajo, using the TELOS (Technical, Economic, Legal, Operational, and Scheduling) analysis. The results of the analysis show that, in general, WIGE craft is feasible for investment for a specific segmented consumer in KNP, Labuan Bajo. This study recommends support from various stakeholders, such as regulators and shipyards, for sustainable operations. For further research, feasibility studies may be conducted on other types of WIGE craft and amphibious aircraft.